The Distribution of The Lumbal Bone Mineral Density Within Turkish Postmenopousal Female Population - Gültekin Köse; Murat Api; Nurettin Aka (Medical Network, 2006)
OBJECTIVE: The aim of this study was to evaluate the distribution of the lumbal bone mineral density within Turkish postmenauposal female population. Models proposed so far f or pathogenesis of osteoporosis often do not take the f actors underly ing the diff erent incidences of v ertebral f ractures in different location in the spinal column and in different populations. STUDY DESIGN: To adress this issue, we analy zed 580 postmenopausal f emale patients in a population-based retrospective study. Bone mineral density (BMD) values found at the lumbal spine were almost similar. Intraclass Correlation Coefficient (ICC) was computed for L1, L2, l3, L4, L2-4. Two-way mixed effect model (ConsistencyDefinition) defined as people effect random and measure effect fixed. Single Measure Intraclass correlation was foun to be 0.9068. RESULTS: The same estimator is used whether the interaction effect is present or not. (95% C.I. Lower=0.8850, Upper=0.9260, F=49.6643, p<0.0001) Cronbach alpha reliability anlaysis showed the mean v ertebral t scores-1.33 (min:-1.45 and max:-1.15 and inret-item correlations mean r=0.9 8min :0.82 and max :0.97). CONCLUSION: Estimated marginal means of measure revealed L3 v ertebra is the most reliable amongst the others and can be used single most effective diagnostic marker in postmenouposal f emale Turkish patients. These results confirm the associaton of BMD in lumbal spines and support the ev idence that lumbal bone density measurements play a signif icant role in the diagnosis of osteoporosis and L3 is the best predictive parameter among those tested.